Energy concentration and positional stability of sonoluminescent bubbles in sulfuric acid for different static pressures - Rosselló, Juan Manuel (2013)
In this study we report several experimental and numerical results on the influence of static pressure (P0) over the main parameters in single bubble sonoluminescence (SBSL), using a sulfuric acid aqueous solution (SA) with low concentrations of argon gas dissolved. Bifrequency driving was used in the experiments to enhance spatial stability of the bubbles. The experimental results were compared with simulations provided by a numerical code that models the radial dynamics of the bubbles. The results showed that an increase on the static pressure of the system shifts the Bjerknes instability threshold, allowing the bubble to access higher acoustic pressures (PAc). Furthermore, a decrease in the measured ambient radius R0 and the calculated relative gas concentration c∞/c0 were observed. A notorious increment in the bubble collapse violence and energy focusing for P0 above 1 bar was achieved. These were mainly indicated by the growth of the bubble expansion ratio (Rmax/R0), the bubble mechanical energy density, and the maximum bubble wall velocity dR/dt. In agreement with the previous statement, the maximum temperature during the bubble collapse predicted by the model is augmented as well. The use of different harmonics in the ultrasound pressure field regarding energy focusing is also discussed. Finally, we analyzed the stability regions of the R0-PAc parameter space via numerical predictions for P0 above the measured, identifying the shape instabilities as the main limiting agent to obtain further energy concentration in SA systems at high static pressures.